Euglenoid flagellates: a multifaceted biotechnology platform - Krajčovič, Juraj; Matej Vesteg; Schwartzbach, Steven D (Journal of biotechnology, 2015)
Euglenoid flagellates are mainly fresh water protists growing in highly diverse environments making them well-suited for a multiplicity of biotechnology applications. Phototrophic euglenids possesses complex chloroplasts of green algal origin bounded by three membranes. Euglena nuclear and plastid genome organization, gene structure and gene expression are distinctly different from other organisms. Our observations on the model organism Euglena gracilis indicate that transcription of both the plastid and nuclear genome is insensitive to environmental changes and that gene expression is regulated mainly at the post-transcriptional level. Euglena plastids have been proposed as a site for the production of proteins and value added metabolites of biotechnological interest. Euglena has been shown to be a suitable protist species to be used for production of several compounds that are used in the production of cosmeceuticals and nutraceuticals, such as α-tocopherol, wax esters, polyunsaturated fatty acids, biotin and tyrosine. The storage polysaccharide, paramylon, has immunostimulatory properties and has shown a promise for biomaterials production. Euglena biomass can be used as a nutritional supplement in aquaculture and in animal feed. Diverse applications of Euglena in environmental biotechnology include ecotoxicological risk assessment, heavy metal bioremediation, bioremediation of industrial wastewater and contaminated water.
Keywords: Cosmeceuticals; biodegradace; Tocopherol; Genome, Protozoan; Models, Biological; potravní doplňky; Euglena; Paramylon; Biotechnology; Chloroplasts; biologické modely; buněčné jádro; Cell Nucleus; Wax esters; Ecotoxicology; Dietary Supplements; kosmeceutika; fylogeneze; genom protozoální; biotechnologie; Biodegradation, Environmental; Phylogeny; chloroplasty